(untitled) (Journal of Contemporary Studies, 2022)
Quad or Quadrilateral Security Dialogue, a group of four democracies, the US, India, Japan, and Australia, was first proposed in 2007 by Japanese Prime Minister Shinzo Abe in his ‘confluence of two seas’ speech that subsequently embarked on the path to the foundation of the group. Quad perceives China’s economic growth, which enables her to transform the world order as a threat and aims at containing the growing Chinese assertiveness in the IndoPacific region. The Malabar naval exercises in the Indian Ocean by the Quad members were one such exercise. This paper, aims to analyze the formation of Quad and will contemplate whether the group is causing confrontation or stability in the Asia-Pacific and Indo-Pacific regions. The paper will also assess that the Quad is designed to counter China’s growing influence in the Asia- pacific and Indo-pacific regions. Containing China is likely to create a confrontation in the region.